Simply raw : meat, fish, vegetables - Bonomi, Liliana; Masci, Sandro; Romagnoli, Federica (White Star Publishing, 2012)
In this book devoted to raw food cuisine, there are 110 recipes coming from various culinary traditions, from Mediterranean cuisine and on to American and Oriental cuisines, revisited in the light of new raw food trends